Avaliação do consumo energético em aviários Dark House, com e sem isolamento térmico: um estudo de caso na região de Palotina, Paraná - Bedin, Janaina (2015)
The production of poultry cuts suffered major investments in technology and genetic development in recent decades, trying to adapt to the conditions and requirements of the national and world market. Studies on the production through the analysis of systems and means of accommodation, show the economic importance of the sector, which has established itself as one of the most competitive in the agribusiness sector. The present work was the study of two aviaries dark house, with and without thermal insulation in their construction, are located in the city of Palotina, Paraná, trying to evaluate the variations in temperature, gas consumption and animal performance of the two systems . In terms of methodology, both facilities were checked temperature variation, with reading by J-type thermocouple sensors and recording in datalogger; consumption of LPG, with installation of individual volumetric meters; and the animal performance and the elimination of mortality and birds, feed intake and water and weight gain. At the end of the study it can be concluded that the aviary Dark House with Thermal Insulation (DHIT) showed better animal performance indexes, lower mortality and elimination, and greater weight gain. But when evaluated performance in the face of temperature conditions, the aviary Dark House Conventional (DHC) showed better suited to the production values, as bibliographic references.